The Sublime in the Miserable and Disgusting Remains of a Dead Body: The Paradoxical “Beauty” of the Relic and its Textile Wrapping in Medieval Times (Itinera, 2024)
In medieval literature the physical remains of martyrs and saints are described as shining gems, or fragrant flowers in the name of a spiritualiter apprehension for which the brute and disgusting matter of bones or mummified flesh is elevated to the highest good and highest beauty, that is, to the status of “relic”. The faithful-spectator therefore experiences a conversion of vision to which the reliquary contributes with its sensual guise and its dialectic of hiding/showing.Even the precious textiles that wrap the relics play an active role in this ethical-aesthetic mediation, being capable of triggering symbolic associations gravitating around the Christian theology of clothing. The starting point is the parallelism established by Thiofrid of Echternach († 1110) between the reliquary and the appearances of the Eucharistic bread and wine defined as velamen placed to cover the substance of the body and blood of the crucified Christ which, if shown, would have disgusted the faithful.A quick foray into contemporary art will demonstrate the persistent vitality of the notion of relic and the mechanism of veiling/dressing that belongs to the reliquary, to this powerful device for presenting the unpresentable.
Keywords: Relic and Reliquary, Disgust, Thiofrid of Echternach, Velamen, Textiles, Sublimation, Vestimentary Metaphor